Target Costing to Manage Production Cost in Cassava Fermented SMEs Case in “Kembang Madu” Tapay Industry – Indonesia - Kustono, Alwan Sri; Mas’ud, Imam; Magvira, Dwima Nadya (Proceeding UII-ICABE, 2020)
The purpose of this research is to study how target costing implementation on managing production cost in cassava fermented industry: “Kembang Madu” tapay, in order to reach the desired proftt. The difficulties on managing cost and getting desired profit in “Kembang Madu” tapay was the reason and motivation behind this research. To get all the data that needed in this research, researcher choose to do observation and interviewing the production manager and the owner of “Kembang Madu” tapay. The production cost calculated the company and the alternative production cost calculated by researcher, were analyzed and compared each other to know how good the target costing implementation. The result of this research shows that target costing implementation in “Kembang Madu” tapay was good and fit. Implementation of target costing can raise the profit earned as much as the desired profit. And then, the company can manage the production cost on its product. Keywords: production cost, profit target, target costing, selling price